Differing Approaches to Religious Benefaction: The Late Third-Century Acquisition of the Sardis Synagogue - Bonz, Marianne Palmer (Harvard theological review, 1993)
Although it was discovered in 1962 and its excavation was completed by the mid-1970s, the synagogue of ancient Sardis in western Asia Minor, with its nearly eighty Greek inscriptions, remains the single most important archaeological source for our knowledge of western diasporan Judaism and its relationship to the wider Greco-Roman world. Despite its historical importance, however, scholars have rarely questioned the assumptions and conclusions of its original interpreters, Andrew Seager and Thomas Kraabel. Yet, for example, on the crucial question of dating (that is, when the building actually became a synagogue) these authors clearly disagreed among themselves, as is evident from a careful reading of their jointly written analysis, published in 1983. Their long-awaited report on the Sardis synagogue may clarify this question as well as other important issues. At present, however, confusion abounds in the secondary literature, because in general this literature continues to accept uncritically Kraabel's selection and interpretation of the relevant evidence. Although I have reexamined the major aspects of the question of dating in a previous article, as has Helga Botermann independently and in more detail, the analysis of the building history reflected in this present article is also indebted to John H. Kroll's excellent but still unpublished manuscript of the Greek inscriptions.